The Influence of Bacteria on the Growth, Lipid Production, and Extracellular Metabolite Accumulation by Phaeodactylum tricornutum (Bacillariophyceae). Issue 3 (4th March 2021) - Chorazyczewski, Adam M.; Huang, I‐Shuo; Abdulla, Hussain; Mayali, Xavier; Zimba, Paul V.
Abstract : To examine the impact of heterotrophic bacteria on microalgal physiology, we co‐cultured the diatom Phaeodactylum tricornutum with six bacterial strains to quantify bacteria‐mediated differences in algal biomass, total intracellular lipids, and for a subset, extracellular metabolite accumulation. A Marinobacter isolate significantly increased algal cell concentrations, dry biomass, and lipid content compared to axenic algal cultures. Two other bacterial strains from the Bacteroidetes order, of the genera Algoriphagus and Muricauda, significantly lowered P. tricornutum biomass, leading to overall decreased lipid accumulation. These three bacterial co‐cultures (one mutualistic, two competitive) were analyzed for extracellular metabolites via untargeted liquid chromatography mass spectrometry to compare against bacteria‐free cultures. Over 80% of the extracellular metabolites differentially abundant in at least one treatment were in higher concentrations in the axenic cultures, in agreement with the hypothesis that the co‐cultured bacteria incorporated algal‐derived organic compounds for growth. Furthermore, the extracellular metabolite profiles of the two growth‐inhibiting cultures were more similar to one another than the growth‐promoting co‐culture, linking metabolite patterns to ecological role. Our results show that algal–bacterial interactions can influence the accumulation of intracellular lipids and extracellular metabolites, and suggest that utilization and accumulation of compounds outside the cell play a role in regulating microbial interactions.